Protocol for a phase IV, open-label feasibility study investigating non-invasive markers of hepatic fibrosis in people living with HIV-1 and non-alcoholic fatty liver disease randomised to receiving optimised background therapy (OBT) plus maraviroc or OBT alone. Issue 7 (6th July 2020) - Bradshaw, Daniel; Gilleece, Yvonne; Verma, Sumita; Abramowicz, Iga; Bremner, Stephen; Perry, Nicky
Abstract : Introduction: At least 30% of people living with HIV (PLWH) infection have non-alcoholic fatty liver disease (NAFLD), which has now become a leading cause of hepatic fibrosis and cirrhosis. Management is based largely on lifestyle modifications, which are difficult to achieve, and therapeutic options are urgently needed. Maraviroc (MVC), through antagonism of CCR5 receptors, may reduce hepatic fibrosis progression and could be an effective treatment for NAFLD. However, dosing is usually two times per day, unlike most currently recommended antiretroviral therapies. This study will investigate the feasibility and acceptability of addition of MVC to combination antiretroviral therapy in PLWH and NAFLD as a treatment for NAFLD. Methods and analysis: This is a phase IV, randomised, open-label, non-invasive feasibility study. Sixty individuals with well-controlled HIV-1 and NAFLD will be recruited from UK HIV clinics and randomised 1:1 to receive either optimised background therapy (OBT) plus MVC or OBT alone. Follow-up will be every 24 weeks for 96 weeks. The primary outcome measures will include recruitment and retention rates, adverse events and adherence. Secondary outcomes will include changes in markers of hepatic fibrosis, including the Enhanced Liver Fibrosis score, median liver stiffness measurement and controlled attenuation parameter scores on Fibroscan, and quality of life assessments. Analyses will be performed according to intention-to-treat principles. For secondary outcomes, estimated differences and 95% CIs between the groups using a t-method will be presented for continuous variables and as exact 95% binomial CIs for categorical variables. Ethics and dissemination: Ethical approval was obtained through the London Dulwich UK Research Ethics Committee (reference 17/LO/2093). Results will be disseminated both through community groups and peer-reviewed scientific literature. Trial registration number SRCTN31461655. EudraCT number 2017-004141-24; Pre-results.